The Effect of Turmeric-Tamarind Administration on the Reduction of Dysmenorrhea in Adolescents at Posyandu Ciseureuh Purwakarta - Humaeroh, Dita (CV. Publikasi Indonesia, 2025)
This quasi-experimental study aimed to determine the effect of turmeric-tamarind administration on reducing dysmenorrhea in adolescent girls at Posyandu Ciseureuh Purwakarta. A total of 40 adolescent girls who met the inclusion criteria were randomly selected and divided into two groups: the intervention group, which received turmeric-tamarind administration, and the control group, which did not receive the intervention. Pre-test and post-test assessments were conducted using the Numerical Rating Scale (NRS) to measure pain levels before and after the intervention. The results indicated a significant reduction in dysmenorrhea pain in the intervention group compared to the control group. This study suggests that turmeric-tamarind administration can effectively reduce dysmenorrhea pain in adolescents, offering a non-pharmacological alternative for pain management during menstruation. These results have important practical implications for adolescent healthcare. First, they provide evidence supporting the integration of this affordable, culturally acceptable traditional remedy into community health programs. Second, the study offers a viable non-pharmacological alternative to pain management that avoids side effects associated with conventional analgesics. For healthcare providers, these findings suggest the potential for developing standardized protocols for turmeric-tamarind administration in managing primary dysmenorrhea. Future research should explore optimal dosage and long-term effects to facilitate wider implementation of this intervention in public health settings.